Anthraquinone and xanthone derivatives from propolis of Tetragonula laeviceps stingless bee: Anthraquinones and xanthones from Tetragonula laeviceps propolis - Le, Nguyen Thanh; Diep, Thi Lan Phuong; Vu, Thi Hue; Nguyen Thi Hue; Nguyen, Hoang Nam; Nguyen, Thanh Cong; Nguyen, Thi Phuong Lien; Dinh, Ngoc Thuc; Nguyen, Quoc Vuong (Vietnam Journal of Science and Technology, 2025)
Stingless bees, that lack a functional sting, are distributed throughout most of the tropical and subtropical regions of the world such as South America, Africa, Australia and Southeast Asia. Tetragonula laeviceps (Smith, 1857) is a species of stingless bee found in Southeast Asian countries. The extracts of T. laeviceps propolis showed many biological effects but chemical study of T. laeviceps propolis has been very limited. Chemical investigation of T. laeviceps propolis collected in Hoa Binh province led to the isolation of nine known compounds including emodin (1), 3-geranyloxy emodin (2), 1,3,7-trihydroxy-2,4-bis(3-methylbut-2-enyl)xanthone (3), cudratricusxanthone F (4), 9-hydroxycalabaxanthone (5), α-mangostin (6), γ-mangostin (7), 1,3,5-trihydroxy-4-geranylxanthone (8) and pruniflorone I (9). Their structures were elucidated by MS and NMR spectral analysis and comparison with those reported in literatures. This is the first investigation of T. laeviceps propolis in Vietnam. Compounds 1-4, 8 and 9 were found from stingless bee propolis for the first time.